Create or Die : Essays on the Artistry of Dennis Hopper - Naish, Stephen Lee (Book collections on Project MUSE., 2016)
Dennis Hopper (1936-2010) was one of most charismatic and protean figures to emerge from the American independent film movement of the 1960s and '70s, an incredibly compelling screen presence who helped give cult classics like Easy Rider and Blue Velvet their off-kilter appeal. But his artistic interests went far beyond acting, and this collection of essays is the first major work to take in Hopper as a creative artist in all his fields of endeavour, from acting and directing to photography, sculpture, and expressionist painting. Stephen Naish doesn't skimp on covering Hopper's best-known work, but he breaks new ground in putting it in context with his other creative enterprises, showing how one medium informs another, and how they offer a portrait of an artist who was restless, even flawed at times, but always aiming to live up to his motto: create or die.[-][-]Follow the podcasts by Steve Naish here.